Reforming Indonesia’s Tax Administration: A Constitutional and Institutional Analysis of the Directorate General of Taxes’ Transformation into a Semi-Autonomous Tax Revenue Agency - Fatmawati Fatmawati; Febrian Febrian; Ridwan Ridwan (Greenation Research & Yayasan Global Resarch National, 2026)
This study examines the organizational model of the Directorate General of Taxes (DGT) following its proposed revitalization into a Tax Revenue Agency within the Indonesian government. Currently, the DGT’s institutional design faces significant dependency issues due to its status as an Echelon I unit under the Ministry of Finance. This dependency creates obstacles such as limited authority to independently manage budgets and human resources, bureaucratic red tape, and the potential for political interference in policymaking. Employing a normative legal research method with a statutory approach, this study finds that transforming the institution into a semi-autonomous agency (SARA) model independent and directly accountable to the President could substantially enhance the effectiveness and efficiency of tax administration. This semi-autonomous model is projected to optimize the tax authority's performance in boosting state revenue and narrowing the tax compliance gap. As a recommendation, this complex and high-risk structural transformation requires a robust legal foundation established through new legislation. Furthermore, its success hinges on consistent political commitment from the nation's top leadership, the creation of rigorous accountability mechanisms such as an oversight board and well-prepared transition safeguards to manage every stage of the organizational change.